1975
DOI: 10.1021/i360056a005
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Asphaltenes on Asphalt Viscosity

Abstract: He received the equivalent to the B.S. degree from the University of Mainz, Germany, in 1952 and the Ph.D. degree from the same university in 1958. After two years as a research associate at the Massachusetts Institute of Technology he joined Chevron Research Company in 1961. He is the author and coauthor of several publications and patents concerning the fractionation and characterization of polymers and other large molecules and their use in industrial applications. He is a member of the American Chemical So… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0

Year Published

1979
1979
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(41 citation statements)
references
References 11 publications
2
39
0
Order By: Relevance
“…It has been shown that the asphaltene fraction is mainly responsible for large viscosity of heavy crude oils or residues [2,33] and the colloidal particle suspension approach has been used in order to explain the viscosity dependence on asphaltene concentration [34,35]. In this approach, the relative viscosities η r of asphaltene suspensions, defined as the ratio of the solution viscosity η to that of pure solvent η 0 , are measured as a function of the volume fraction φ of the solute.…”
Section: Viscositymentioning
confidence: 99%
“…It has been shown that the asphaltene fraction is mainly responsible for large viscosity of heavy crude oils or residues [2,33] and the colloidal particle suspension approach has been used in order to explain the viscosity dependence on asphaltene concentration [34,35]. In this approach, the relative viscosities η r of asphaltene suspensions, defined as the ratio of the solution viscosity η to that of pure solvent η 0 , are measured as a function of the volume fraction φ of the solute.…”
Section: Viscositymentioning
confidence: 99%
“…The second model is to see asphaltenes solutions like insoluble and solid particles maintained in solution by resins. They are adsorbed on asphaltenes particles, providing a steric stabilization [7].…”
Section: Small Angle X-ray Scattering (Saxs) Measurementsmentioning
confidence: 99%
“…The state of dispersion is dependent upon the affmity between maltene and asphaltene molecules. Altgelt et al (1975) Therefore, the large viscosity activation energy dependence on asphaltene content for high saturates content can be explained largely as a result of a relatively large reduction in solvation power of aromatics/saturates mixture due to saturate crystalline formation.…”
Section: Resultsmentioning
confidence: 99%
“…This sharp increase in viscosity with increased asphaltenes is due to the low solvation power of the dispersing media with excessive amount of saturates. As described by colloidal models (Altgelt et al, 1975), asphaltene molecule aggregation is strongly influenced by the solvent power of the maltene phase.…”
Section: Effects Of Saturates In the Presence Of Original Asphaltenementioning
confidence: 99%